Ecological Studies of Desert Soils of Churu, Rajasthan (India): pH Status - Sharma, B.M. (Journal of Soil and Water Conservation, 2022)
Hydrogen ion concentration is a diagnostic -figure of unique value having implications as to the fertility of soils. It gives an initial clue to the chemical characteristics of a soil. It has a considerable influence not only upon the solubility of nutrients but also upon the facility with which these nutrients, even when already in solution, are absorbed and used by plant (Lyon et al, 1954). Pearsall (1952) states "It may be safely said that the soil pH remains the most powerful single measurement for ecological purposes".